The SAGE handbook of youth work practice - Alldred, Pam; Cullen, Fin; Edwards, Kathy; Fusco, Dana (London Sage, 2018)
Showcases the value of professional work with young people as it is practiced in diverse forms, and in locations from around the world.
"SAGE Reference".
Includes bibliographical references and index.
Keywords: Social work with youth; Youth workers; Social work with youth; Youth workers